2020
DOI: 10.3390/md18110529
|View full text |Cite
|
Sign up to set email alerts
|

Diphlorethohydroxycarmalol (DPHC) Isolated from the Brown Alga Ishige okamurae Acts on Inflammatory Myopathy as an Inhibitory Agent of TNF-α

Abstract: Inflammation affects various organs of the human body, including skeletal muscle. Phlorotannins are natural biologically active substances found in marine brown algae and exhibit anti-inflammatory activities. In this study, we focused on the effects of phlorotannins on anti-inflammatory activity and skeletal muscle cell proliferation activity to identify the protective effects on the inflammatory myopathy. First, the five species of marine brown algal extracts dramatically inhibited nitric oxide (NO) productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Next, the proliferation effect of skeletal muscle cells was measured during the differentiation period by BrdU cell proliferation assay [ 19 , 20 , 21 , 22 ], except for compound 9 , which was excluded because of its toxicity. Compared to the control conditions, most compounds triggered approximately a 1.2-fold increase in cell proliferation ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…Next, the proliferation effect of skeletal muscle cells was measured during the differentiation period by BrdU cell proliferation assay [ 19 , 20 , 21 , 22 ], except for compound 9 , which was excluded because of its toxicity. Compared to the control conditions, most compounds triggered approximately a 1.2-fold increase in cell proliferation ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported the various biological activities mediated by IO, including anti-obesity, anti-diabetes, and anti-inflammatory properties [ 28 , 29 ]. A previous study showed that IO downregulated pro-inflammatory cytokines and muscle atrophy proteins against TNF-α, thereby demonstrating its potential as a TNF-α inhibitor for inflammatory myopathy [ 21 ]. In addition, IO improved the proliferation of C2C12 myoblasts [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ishige okamurae extract (IO) has been reported to activate skeletal muscle cell proliferation without inducing cytotoxicity in C2C12 myoblasts [ 20 ]. In addition, IO can potentially inhibit tumor necrosis factor (TNF)-α in muscle-degradation-induced inflammatory myopathy [ 21 ]. However, the underlying mechanism of action of IPA, which is the equivalent content of IPA in IO, on muscle function in Dexa-induced muscle atrophy remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Resulting from those effects, they suppressed the production of PGE 2 , IL-1β, IL-6, TNF-α, and monocyte chemoattractant protein-1 (MCP-1) and expression of COX-2 and iNOS. [93][94][95][96][97] Although PFF-B's effects were mentioned above, there are reports by other research groups. PFF-B suppressed expression of COX-2 and iNOS and production of NO, IL-1β, and IL-6 and the effect was attributed to the degradation of the NF-κB signaling pathway through the suppression of Akt, ERK, and JNK phosphorylation.…”
Section: Other Phlorotanninsmentioning
confidence: 94%